2022
DOI: 10.1001/jamanetworkopen.2022.12347
|View full text |Cite|
|
Sign up to set email alerts
|

Survival Outcomes Associated With Cytoreductive Nephrectomy in Patients With Metastatic Clear Cell Renal Cell Carcinoma

Abstract: IMPORTANCELevel I evidence has failed to demonstrate an overall survival (OS) advantage for cytoreductive nephrectomy in patients with metastatic clear cell renal cell carcinoma (ccRCC) in the modern era, which is at odds with observational studies reporting a marked OS benefit associated with these operations. These observational studies were not designed to adjust for unmeasured confounding.OBJECTIVE To assess whether cytoreductive nephrectomy is associated with improved OS in patients with metastatic ccRCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Recently, data from a cohort study from the National Cancer Database published by Chakiryan et al did not demonstrate a survival benefit for CN in patients with mRCC using instrumental variable analysis [ 46 ]. The authors claim that the indication for CN is primarily driven by factors that are not reflected in observational studies, leading to confounding results.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, data from a cohort study from the National Cancer Database published by Chakiryan et al did not demonstrate a survival benefit for CN in patients with mRCC using instrumental variable analysis [ 46 ]. The authors claim that the indication for CN is primarily driven by factors that are not reflected in observational studies, leading to confounding results.…”
Section: Discussionmentioning
confidence: 99%
“…At present, positive associations between cytoreductive resection of primary tumors and superior overall survival rates have been demonstrated in a variety of solid metastatic tumors, such as advanced-stage endometrial cancer, cohesive gastric cancer, and ovarian cancer (20)(21)(22). As for mccRCC, a significant survival benefit associated with CN and systemic therapy was found in a study by Chakiryan et (23)(24)(25).…”
Section: Discussionmentioning
confidence: 97%
“…Overall, 70% (n=550) of the patients were randomly divided into the training cohorts, while the remaining 30% (n=232) were assigned to the internal test cohort. The median follow-up was 25 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) months in the SEER database. A total of 144 patients were included in the external test (PUMCH) cohort, and the median follow-up for this cohort was 37 (24-52) months.…”
Section: Baseline Characteristicsmentioning
confidence: 99%
“…The pendulum has swung back and forth, with evidence supporting it in the cytokine era [9,10] and mixed results now in the context of targeted therapy. Although the CARMENA trial [11] found that upfront cytoreductive nephrectomy in Memorial Sloan-Kettering Cancer Center (MSKCC) intermediate-to-poor risk patients who require systemic therapy did not confer survival benefit, evidence from recent retrospective propensity-matched studies using large national databases suggest otherwise [12 ▪ –14 ▪ ]. With regard to the timing of cytoreductive nephrectomy, while the SURTIME trial [15] found significant survival benefit conferred by delayed versus upfront cytoreductive nephrectomy, two recent database studies [13 ▪ ,14 ▪ ] found no difference in overall survival (OS).…”
Section: Kidney Cancermentioning
confidence: 99%